2013
DOI: 10.1021/cg4007108
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Structural Analysis of Turn Modified cyclo-(αβ3αβ2α)2 Peptide Derivatives toward Crystalline Hexagon-Shaped Cationic Nanochannel Assemblies

Abstract: Synthesis and characterization of peptides 3-17.General methods: (S)-Fmoc-β 3 -homoleucine-OH and (R)-Fmoc-2-aminodecanoic acid were obtained from Senn Chemicals AG. Solvents and chemicals were used as received from their supplier. Solvents were stored over 4 Å molecular sieves. Solvents for column chromatography and extractions were of technical grade and distilled prior to use. THF was distilled over LiAlH 4 , CH 2 Cl 2 over CaH 2 and MeOH over NaBH 4 prior to use. All reactions were performed at room temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 56 publications
(50 reference statements)
0
11
0
Order By: Relevance
“…Synthesis of gramicidin S and analogues : The synthesis, characterization, and crystallographic structural studies of gramicidin S ( 1 ) and GS analogues 4 – 8 were previously reported in the literature 3436. GS analogues 2 and 3 were synthesized with an adaptation of a previously reported method 30.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Synthesis of gramicidin S and analogues : The synthesis, characterization, and crystallographic structural studies of gramicidin S ( 1 ) and GS analogues 4 – 8 were previously reported in the literature 3436. GS analogues 2 and 3 were synthesized with an adaptation of a previously reported method 30.…”
Section: Methodsmentioning
confidence: 99%
“…Synthesis of gramicidin S and analogues: The synthesis, characterization, and crystallographic structural studies of gramicidin S (1) and GS analogues 4-8 were previously reported in the literature. [34][35][36] GS analogues 2 and 3 were synthesized with an adaptation of a previously reported method. [30] All peptides were synthesized by using a standard 9-fluorenylmethoxycarbonyl (Fmoc) protection peptide synthesis protocol, involving the assembly of the protected linear decapeptides on a solid support, mild acidic cleavage, and macrocyclization in solution by using PyBOP/ HOBt/DiPEA in DMF at high dilution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the start of user operation until March 2014, 60 research groups have tested 8363 crystals and collected 3281 datasets (defining one dataset as having 90 or more image frames), which has allowed the users to solve a large variety of structures that include integral membrane proteins or large-unit-cell crystals. As a result, the scientific production has started in earnest with the first structures being deposited in the Protein Data Bank and the first papers being published in peer-reviewed journals (Bacarizo & Camara-Artigas, 2013;Gallego et al, 2013;Gallego del Sol & Marina, 2013;Otero et al, 2013).…”
Section: First Resultsmentioning
confidence: 99%
“…The structure of GS identified by crystallography [129] was shown to dock into the β-hairpin-like structure of Aβ(18-42) with its hydrophobic and hydrophilic residues interacting, respectively, with the apolar hydrophobic and polar hydrophilic interfaces within the amyloidogenic fibrillar tubes [106]. A family of mixed (αβαβα) 2 cyclopeptides was designed based on GS and shown to form β-hairpin-like structures [131] that fit the channel interface of Aβ better than GS, probably because of the increased flexibility [106]. Further ThT assays and docking simulations performed on the GS derivatives illustrated the importance of hydrophilic and aromatic residues for interactions with the fibrils.…”
Section: Gramicidin S and Derivativesmentioning
confidence: 99%